Superhydrophobic and oleophobic coatings from flower‐like zinc oxide and fluorinated epoxy with good comprehensive property. (9th November 2022) - Li, Ruhui; Huang, Xiaoye; Yu, Ruobing
Abstract : Nowadays, most superhydrophobic surfaces will lose their superhydrophobic performance once they encounter oil, and adhesive strength of superhydrophobic coating is low. Therefore, the superhydrophobic coating with good oleophobicity and high adhesive strength is popular with people. A superhydrophobic and oleophobic coating is characteristic of antifouling and self‐cleaning, due to the appearance of special structures, such as overhang and re‐entrant. In this work, flower‐like zinc oxide (ZnO) particles free of fluorine and fluorine‐containing epoxy were used to establish the coating with a similar re‐entrant structure. Flower‐like ZnO particles were prepared by a chemical precipitation method, and the water contact angle of flower‐like ZnO is up to 149 ± 1°. For the coating, flower‐like ZnO particles were almost covered by fluorine‐containing epoxy synthesized through click reaction so that the adhesive strength between the coating and the matrix is high, superior to some coatings in the references. The surfaces made of flower‐like ZnO and fluorinated epoxy possess superhydrophobic and oleophobic properties. The contact angle of the coating for water, diiodomethane, glycerol, and glycol is 154 ± 0.7°, 138 ± 0.6°, 156 ± 0.7°, and 150 ± 0.7°, respectively. After withstanding 70 cycles under the pressure of 1 kPa, the coating is still superhydrophobic. Also, the coating possesses a good self‐cleaning and anti‐icing property.